Initiation of contact tracing for Covid-19 at an academic institution for health science: initial experiences - Paudel, Rajan; Upadhyaya, Dipak Prasad (Journal of Chitwan Medical College, 2020)
Transmission of COVID-19 cases has been found in clusters and sporadic form in different parts of Nepal, which swiftly strained the healthcare system. Contact tracing is a strategy to prevent further transmission of the COVID-19. It reduces the overwhelming burden in a health system. Academic institutions are the best alternative in contact tracing, not only in terms of task shifting but their training in epidemiology and research also best suits them. Besides, they can also train the health workers assigned for contact tracing in rural and urban settings. Multi-sectoral involvement from academia, community health workers, and effective information flow are instrumental for effective contact tracing in resource-limited settings.